2021
DOI: 10.3389/fpls.2021.701529
|View full text |Cite
|
Sign up to set email alerts
|

Five OsS40 Family Members Are Identified as Senescence-Related Genes in Rice by Reverse Genetics Approach

Abstract: A total of 16 OsS40 genes of Oryza sativa were identified in our previous work, but their functions remain unclear. In this study, 13 OsS40 members were knocked out using the CRISPR/cas9 gene-editing technology. After screening phenotype characterization of CRISPR/Cas9 mutants compared to WT, five oss40s mutants exhibited a stay-green phenotype at 30 days after heading. Moreover, increased grain size and grain weight occurred in the oss40-1, oss40-12, and oss40-14 lines, while declined grain weight appeared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…Down-regulation of owering related genes i.e., FLOWERING PROMOTING FACTOR 1 (FPF1), EARLY FLOWERING 3 (ELF3), and AGAMOUS-LIKE MADS-BOX PROTEIN (AGL12, SVP) support late maturing, higher biomass and sugars in HB genotypes. Leaf senescence is an important terminal stage of plant development after reproductive phase, senescence related NAC transcription factors and a newly identi ed S-40 gene family also showed down-regulation [52,53]. The expression levels of owering and senescence related genes support the notion that HB genotypes undergo extended vegetative phase and delayed reproductive maturity.…”
Section: Discussionmentioning
confidence: 72%
“…Down-regulation of owering related genes i.e., FLOWERING PROMOTING FACTOR 1 (FPF1), EARLY FLOWERING 3 (ELF3), and AGAMOUS-LIKE MADS-BOX PROTEIN (AGL12, SVP) support late maturing, higher biomass and sugars in HB genotypes. Leaf senescence is an important terminal stage of plant development after reproductive phase, senescence related NAC transcription factors and a newly identi ed S-40 gene family also showed down-regulation [52,53]. The expression levels of owering and senescence related genes support the notion that HB genotypes undergo extended vegetative phase and delayed reproductive maturity.…”
Section: Discussionmentioning
confidence: 72%
“…However, other studies showed that S40 protein promoted leaf senescence. Rice OsS40 have been shown to play a role in carbon allocation and leaf senescence in Oryza sativa by modulating the expression of SWEET sugar transporter genes and other senescence-related genes [ 34 ]. Barley HvS40 was used as a biomarker of senescence by playing as a key upstream regulator of a well-known senescence gene SAG expression [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the aid of forwarding or reversing genetics strategies and the development of multi-functional CRISPR genome editing technology, a large number of senescence-related mutants will be generated. For example, quintuple mutants of oss40s-cr generated using CRISPR technology displays stay-green phenotypes ( Habiba et al, 2021 ), which will further deepen our understanding of leaf senescence. The model plant Arabidopsis has played an important role in revealing the molecular or genetic regulation mechanisms of plant senescence, but we still know little about leaf senescence and do not fully understand the biological significance of senescence ( Lim et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%